2014
DOI: 10.5511/plantbiotechnology.14.0117b
|View full text |Cite
|
Sign up to set email alerts
|

The longer version of Arabidopsis thaliana heat shock protein 18.2 gene terminator contributes to higher expression of stably integrated transgenes in cultured tobacco cells

Abstract: In order to achieve higher expression of a transgene, it is important to optimize not only the promoter, 5′-untranslated region (UTR), and localization signal, but also the transcriptional terminator. We previously reported that the terminator derived from the Arabidopsis thaliana heat shock protein 18.2 gene (HSPT) increases gene expression in various plant species. In this study, with the goal of further increasing the expression level of transgenes, we evaluated a longer version of HSPT, corresponding to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 17 publications
0
21
0
Order By: Relevance
“…Perhaps it is also due to APA events, allowing fine regulation of expression (Takagaki et al, 1996;Tang et al, 2002;Quesada et al, 2003;Simpson et al, 2003;Delaney et al, 2006;Dong et al, 2007;Ji et al, 2009;Tian and Manley, 2013). Matsui et al (2014) demonstrated that the use of a longer version of the HSP 3' regulatory region results in higher levels of expression compared to a smaller version. According to the authors, the high levels of expression achieved in the longer version occurred due to the presence of a matrix attachment region (MAR), ATrich DNA sequences that assist in the chromatin structural organization, being involved in transcriptional control (Abranches et al, 2005;Tetko et al, 2006).…”
Section: Plant 3' Regulatory Regions For Expression Of Target Genesmentioning
confidence: 99%
“…Perhaps it is also due to APA events, allowing fine regulation of expression (Takagaki et al, 1996;Tang et al, 2002;Quesada et al, 2003;Simpson et al, 2003;Delaney et al, 2006;Dong et al, 2007;Ji et al, 2009;Tian and Manley, 2013). Matsui et al (2014) demonstrated that the use of a longer version of the HSP 3' regulatory region results in higher levels of expression compared to a smaller version. According to the authors, the high levels of expression achieved in the longer version occurred due to the presence of a matrix attachment region (MAR), ATrich DNA sequences that assist in the chromatin structural organization, being involved in transcriptional control (Abranches et al, 2005;Tetko et al, 2006).…”
Section: Plant 3' Regulatory Regions For Expression Of Target Genesmentioning
confidence: 99%
“…The resulting plasmid was digested with NsiI, followed by treatment with T4 DNA polymerase to fix the NsiI site and generate AtADH_5′UTR:CpYGFP:HSP-T. Furthermore, a SacI-EcoRI HSP-T878 terminator fragment was excised from AtADHFluc-HSPT878 (Matsui et al 2014) and inserted into the SacIEcoRI gap of AtADH_5′UTR:CpYGFP:HSP-T to generate AtADH_5′UTR:CpYGFP:HSP-T878. An XbaI-EcoRI fragment was excised from AtADH_5′UTR:CpYGFP:HSP-T878 and inserted into the SpeI-EcoRI gap of AtADH_5′UTR: CpYGFP:HSP-T878 to generate 2×CpYGFP.…”
Section: Plasmid Constructionmentioning
confidence: 99%
“…A considerable number of Torenia plants transformed with this improved gene construct (1×CpYGFP) clearly exhibited strong fluorescence observable without using any image-enhancing equipment ( Figure 2D, 1×CpYGFP plants). To gain stronger fluorescence, HSP-T (250 bp) in 1×CpYGFP was replaced with its longer version HSP-T878 (Matsui et al 2014), and the expression cassette was tandemly triplicated (3×CpYGFP; Figure 1, lower). A significant number of Torenia plants transformed with this improved gene construct exhibited an excellent strong fluorescence never observed before ( Figure 2E, 3×CpYGFP plants).…”
Section: Generation Of Fluorescent Torenia Flowersmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, we designed an expression cassette in which the coding sequence of eYGFPuv was driven by the cauliflower mosaic virus (CaMV) 35S promoter combined with the transcriptional terminator of the heat shock protein 18.2 (HSP) gene of A. thaliana (HSP-T878) 24 and the 5′ untranslated region (5′UTR) of cold-regulated 47 (COR47) in A. thaliana (COR47-5′UTR) 25 . HSP-878 and COR 47-5′UTR have been reported to increase the expression level of the transgene compared to other transcriptional terminators and translational enhancer, and high accumulation of FPs is expected.…”
Section: Introductionmentioning
confidence: 99%